Increased occurrence of native septic arthritis in adult cirrhotic patients: a population-based three-year follow-up study in Taiwan - Hung, Tsung-Hsing; Hsieh, Min-Hong; Lay, Chorng-Jang; Tsai, Chih-Chun; Tsai, Chen-Chi (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Due to impairment of immunity and metabolism, cirrhotic patients are prone to infection, osteoporosis, and osteonecrosis. However, it is unknown if cirrhotic patients are prone to native septic arthritis (NSA). Aim : To assess the occurrence of NSA between cirrhotic and non-cirrhotic patients. Material and methods : We used the Taiwan National Health Insurance Database to enrol 35,106 cirrhotic patients and 33,457 non-cirrhotic patients from January 1, 2004 to December 31, 2004. The medical record of each patient was individually followed for a 3-year period. Results : There were 341 (0.5%) patients having NSA in a follow-up period of 3 years: 214 cirrhotic and 127 non-cirrhotic patients. The incidence density of hospitalisation for NSA was 2.03 episodes/1000 person-years in cirrhotic patients, and 1.27 episodes/1000 person-years in non-cirrhotic patients. After adjustment for age, gender, and other comorbid disorders, Cox’s regression analysis showed that cirrhotic patients had a higher occurrence of NSA than non-cirrhotic patients(hazard ratio (HR) = 1.51, 95% confidence interval (CI) = 1.19–1.90; p = 0.001). The patients with complicated cirrhosis were more prone to have NSA than those with non-complicated cirrhosis (HR = 1.46, 95% CI = 1.09–1.96, p = 0.011). Conclusions : This analysis demonstrates that cirrhotic patients have a higher risk of NSA, particularly those with complicated cirrhosis.